2023
DOI: 10.22323/2.22030205
|View full text |Cite
|
Sign up to set email alerts
|

The lab, the space and the meetup: locating technological experimentation in everyday life

Abstract: This article analyzes the role digital pioneer communities play in the localization of everyday technological experimentation based on three sites of practice: the lab, the space, and the meetup. Taking a historical view, it begins with a reconstruction of Stewart Brand’s popularization of the lab discourse. On this basis, the space in the Maker movement as well as the meetup in the Quantified Self and Hacks/Hackers movements is investigated, finally arriving at a reflection on the dynamics that come and go be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…When we discuss hackerspaces, makerspaces, and citizen labs, we often emphasize their physical location and resources that support knowledge sharing, peer learning, and collaborative engagement with technology and science. Hackerspaces are defined as community-organized spaces where people collaborate on projects by sharing resources, expertise, and interest in emerging technologies, science, or digital arts (Capdevila, 2013;Cohendet, 2022;Guthrie, n.d.;Hepp, 2023;Moilanen, 2012;Seo-Zindy & Heeks, 2017). While such spaces and labs facilitate experimentation, hacking, invention, and creative engagement with technology, the question remains: Are these spaces driven by explicit political, social, and public objectives?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we discuss hackerspaces, makerspaces, and citizen labs, we often emphasize their physical location and resources that support knowledge sharing, peer learning, and collaborative engagement with technology and science. Hackerspaces are defined as community-organized spaces where people collaborate on projects by sharing resources, expertise, and interest in emerging technologies, science, or digital arts (Capdevila, 2013;Cohendet, 2022;Guthrie, n.d.;Hepp, 2023;Moilanen, 2012;Seo-Zindy & Heeks, 2017). While such spaces and labs facilitate experimentation, hacking, invention, and creative engagement with technology, the question remains: Are these spaces driven by explicit political, social, and public objectives?…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, hackerspaces support what we I describe as "quasi-public" engagements and experiments closer to what Dickel et al identified as a "situated publics of both certified and noncertified experts in different social contexts and settings that openly experiment with technologies" (Dickel et al, 2019). Rather than a political space for rethinking common goals and interests, such ad hoc gatherings over prototypes support a form of technocratic "folklore" that perpetuates the myth of the "pioneer communities" and their Silicon Valley ethos of innovation disruptive of social and political processes (Hepp, 2023). Hackerspaces then represent politically naïve or even irresponsible "co-production of artefacts" and "civic technoscience" that only "expands the regime of technoscience into society" (Dickel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%